Aza-Based Donor-Acceptor Conjugated Polymer Nanoparticles for Near-Infrared Modulated Photothermal Conversion - Zhang, Guobing; Ma, Suxiang; Wang, Weiwei; Zhao, Yao; Ruan, Jiufu; Tang, Longxiang; Lu, Hongbo; Qiu, Longzhen; Ding, Yunsheng (Frontiers in Chemistry, 2019)
It is highly desired that synthesis of photothermal agents with near-infrared (NIR) absorption, excellent photostability, and high photothermal conversion efficiency are needed for potential applications. Three (D-A) conjugated polymers (PBABDF-BDTT, PBABDF-BT, and PBABDF-TVT) based on aza-heterocycle, bis(2-oxo-7-azaindolin-3-ylidene)benzodifurandione (BABDF) as the strong acceptor, and benzodithiophene-thiophene (BDTT), bithiophene (BT), and thiophene-vinylene-thiophene (TVT) as the donor were designed and synthesized. The conjugated polymers showed significant absorption in the NIR region and a maximum absorption peak at 808 nm by adjusting the donor and acceptor units. Their photothermal properties were also investigated by using poly(ethylene glycol)-block-poly(hexyl ethylene phosphate) (mPEG-b-PHEP) to stabilize the supramolecular aggregations of conjugated polymers. Photoexcited conjugated polymer (PBABDF-TVT) nanoparticles underwent nonradiative decay when subjected to single-wavelength NIR light irradiation, leading to an excellent photothermal conversion efficiency, of 40.7%. This study provides a method to introduce strong acceptor units to design conjugated polymers with high extinction coefficients, excellent photothermal conversion efficiency, good biocompatibility, and high stability.